Parathelphusa pardus, a new species of lowland freshwater crab from swamps in central Sumatra, Indonesia (Crustacea: Brachyura: Gecarcinucidae) - Ng, Peter K. L.; Riady, Rikhi; Windarti, Windarti (Zootaxa, 2016)
A new species of gecarcinucid freshwater crab of the genus Parathelphusa H. Milne Edwards, 1853, is described from freshwater swamp habitats in Pekanbaru, Riau Province, in central-eastern Sumatra, Indonesia. Parathelphusa pardus sp. nov., has a very distinctive colour pattern, and in this respect, resembles P. maindroni (Rathbun, 1902) from Sumatra and Peninsular Malaysia; P. batamensis Ng, 1992, from Batam Island, Indonesia; P. reticulata Ng, 1990, from Singapore; and P. oxygona Nobili, 1901, from western Sarawak. It can be distinguished from these species and congeners by a suite of carapace, ambulatory leg, thoracic sternal and most importantly, male first gonopod characters.